Effect of nitrogen fertilization and cultivar on growth and grain yield of maize (Zea mays L.), Gezira State, Sudan - Mohamed, Abdurrahman; Mohamed, Ibrahim; Daffalla, Ahmed (Gezira Journal of Agricultural Science; Vol 16 No 1 (2018), 2018)
Maize ( Zea mays L.) is the world's third leading cereal crop after wheat and rice. In the last two decades, maize gained more importance as a forage and food crop in the Sudan. The objective of this study was to determine the optimum level of nitrogen that maximizes grain yield of maize. This study was conducted at the Experimental Farm, University of Gezira, during the summer and winter seasons of 2016/2017. Eight treatments, namely, four nitrogen levels (0, 43, 86 and 129 kg N/ha) and two cultivars, namely, Hudeiba 1 and Hudeiba 2 were used. A randomized complete block design (RCBD) with three replicates was used.  Results indicated that nitrogen had a significant (P≤0.05) effect on leaf area index, number of days to 80% silking and number of rows/ear in the winter season only, and number of grains/ear in the summer season only. Cultivars had significant effects (P≤0.05) on number of grains/ear and number of days to 80% silking in the summer and winter seasons, respectively.  The result s also showed that nitrogen had a significant (P≤0.05) effect on grain yield in both seasons. The highest grain yield (2.4 and 2.1 t/ha) was obtained when 86 kg N/ha was applied to Hudeiba1 and Hudeiba 2 in summer and winter seasons, respectively. To maximize grain yield of maize, it could be recommended that 86 kg N/ha should be applied to Hudeiba1 and Hudeiba 2 in both seasons.        محصول الذرة الشامية هو ثالث محصول عالمي يتصدر محاصيل الغلال بعد القمح  والأرز. وفي العقدين الأخيرين أصبح أكثر أهمية في السودان كمحصول غذاء وعلف. تهدف هذه الدراسة إلى تحديد الجرعة المثلى للسماد النتروجينى لزيادة معدل إنتاج محصول الذرة الشامية. أجريت هذه الدراسة بالمزرعة التجريبية جامعة الجزيرة في موسمي صيف وشتاء (2016/2017) تم استخدام صنفي الذرة الشامية حديبة1 وحديبة 2, بتصميم القطاعات العشوائية الكاملة, بثلاث مكررات. استعملت أربعة مستويات من النتروجين (صفر و43 و86 و129 كجم نتروجين/هكتار) ليكون العدد الكلي ثمانية معاملات. أوضحت النتائج ان النتروجين له تأثيراً معنوياً على دليل مساحة الورقة وعدد أيام الإزهار للزهرة المؤنثة وعدد الصفوف في الكوز في موسم الشتاء فقط وكان له تأثيراً معنويا على عدد الحبوب في الكوز في فصل الصيف فقط. كما أظهرت الأصناف تأثيراً معنوياً على عدد الحبوب في الكوز وعدد أيام الأزهار للزهرة المؤنثة في موسمي الصيف والشتاء على التوالي. النتروجين كان له أثراً معنوياً على إنتاجية الحبوب في كلا الموسمين, تحققت أعلى إنتاجية من الحبوب (2.4 و2.1 طن/هكتار) عند إضافة 86 كجم نتروجين/هكتار في فصلي الصيف والشتاء لحديبة 1 وحديبة 2 على التوالي. بناءً على هذه النتائج لتحقيق أعلى إنتاجية من حبوب الذرة الشامية توصي الدراسة بإضافة 86 كجم نتروجين/هكتار لصنفي حديبة 1 وحديبة 2   في كلا الموسمين .